Introducing research methodology : thinking your way through your research project - Flick, Uwe (Los Angeles : SAGE Publishing, 2020)
"Accessible and easy to understand, this book offers an encyclopaedic introduction to research, showing you how to think about every stage involved in a research project. Equipping you with the tools you need to understand research processes, it helps you get to grips with the concepts behind qualitative research methodology - and be ready to apply them. Packed with examples that are directly relevant to the kind of research students undertake, this book helps you develop your academic and research skills and showcases how diverse research can be, with examples across different contexts and with different kinds of data. This third edition offers: - Hands-on guidance about how to develop key academic skills like critical thinking, effective writing and building an argument - Straightforward guidance about interpreting findings, assessing arguments and understanding the wider impact of your work that helps you step confidently into a researcher role - A complete overview of the challenges and opportunities involved in working with new forms of data like social media and online data Supported by a dynamic new website that offers templates for building arguments, additional case studies and dos and don'ts videos, this book is the perfect companion for anyone looking for a clear introduction to research methodology"--
Includes bibliographic reference and index.
Keywords: Social research; Method selection